Effect of Steel Fibers on Mechanical Properties of Cement Stabilized Soil - A. Khattab, Suhail (Anbar Journal of Engineering Sciences, 2012)
Recently, many attempts were made to use steel fiber reinforcement to improve some soil properties. In this research, the effect of steel fibers on the compaction and mechanical properties of cement stabilized soil (silty soil) was studied. Variables such as stabilizer (cement) content, amount and type of steel fibers were studied. Results indicate that the addition of fibers leads to increase in the maximum dry unit weight. On the other hand, a maximum value of unconfined and tensile strength were obtained with the addition of 0.5 % short fiber (FS) and 1.5 % long fiber (FL) respectively.